2023
DOI: 10.1155/2023/4604885
|View full text |Cite|
|
Sign up to set email alerts
|

Fusion of Emotional Thinking and Mental Health of Students in Vocal Music Teaching

Abstract: Vocal psychology belongs to the branch of music psychology, which is the cross-study of vocal art and psychology, and is also a new discipline with both theory and application. Vocal singing uses a thinking, conscious person as an instrument that is necessarily governed by the psyche over the physiology, relying on the brain to direct the movement of the singing muscles and the coordination of the vocal organs. The purpose of this thesis is to explore the application of vocal psychology in vocal singing and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The maturation of physiological functions can catalyze psychological maturity, and reciprocally, psychological advancement can foster physiological maturation (Wang & Fu, 2023). Throughout the entire ontogenetic trajectory of an individual, the cadence of physiological and psychological development necessitates harmonization to coalesce into a relatively rational whole, ensuring the individual's physical and mental development perpetually maintain a balanced and stable state (Yang & Yu, 2023). The secondary school stage epitomizes an exceedingly unique and pivotal phase in the individual growth process, and is also heralded as the golden epoch for secondary school students' growth.…”
Section: Psychological Analysis Of Mathematics Anorexia In Secondary ...mentioning
confidence: 99%
“…The maturation of physiological functions can catalyze psychological maturity, and reciprocally, psychological advancement can foster physiological maturation (Wang & Fu, 2023). Throughout the entire ontogenetic trajectory of an individual, the cadence of physiological and psychological development necessitates harmonization to coalesce into a relatively rational whole, ensuring the individual's physical and mental development perpetually maintain a balanced and stable state (Yang & Yu, 2023). The secondary school stage epitomizes an exceedingly unique and pivotal phase in the individual growth process, and is also heralded as the golden epoch for secondary school students' growth.…”
Section: Psychological Analysis Of Mathematics Anorexia In Secondary ...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%